Legal Protection for Land Owners Whose Land is Illegally Certified Through Land Registration - Lulus Purna Malintang (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This paper analyzes the validity of land registration based on informal land sale and purchase agreements and the legal protection for landowners whose land has been unlawfully registered. The study employs a normative juridical research method. Informal land sale and purchase refers to transactions involving a parcel of land conducted without involving an authorized official as required by law. Such transactions are characterized as agreements between the seller and buyer, evidenced by a deed not prepared by a Land Deed Official (PPAT), with its evidentiary strength relying on mutual acknowledgment and documentation provided by the parties. Land registration based on informal land sale and purchase agreements is invalid as it does not comply with Article 37 paragraph (1) of Government Regulation Number 24 of 1997 on Land Registration, nor does it fulfill the principles of clarity and immediacy, the legal requirements of agreements, or the material and formal conditions for land sale and purchase. Landowners who suffer losses due to the unlawful issuance of land certificates may file a claim for unlawful acts under Article 1365 of the Indonesian Civil Code, seek the cancellation of rights due to administrative defects from the Minister or Head of the Land Office, and file a cancellation claim through the Administrative Court (PTUN).